The RELATIONSHIP OF PAD, DAU, DAK and CAPITAL EXPENDITURE DURING THE PANDEMIC IN SLEMAN: RELATIONSHIP OF PAD, DAU, DAK and CAPITAL EXPENDITURE DURING THE PANDEMIC IN SLEMAN - Susi Siswati (Universitas Sarjanawiyata Tamansiswa, 2022)
ABSTRACT This study aims to determine the effect of Regional Original Income, General Allocation Funds, Special Allocation Funds on capital expenditure during the pandemic (Covid 19) in Sleman Regency. The research method used is purposive sampling method. The study used 86 villages from 17 sub-districts in Sleman Regency. The data is obtained from the APBD realization report for the 2019-2020 period. The data analysis method used is simple and multiple regression analysis. Based on simple regression analysis, each of the independent variables partially, namely Regional Original Income, General Allocation Funds, Special Allocation Funds has a significant effect on capital expenditure during the pandemic (Covid 19) in Sleman Regency so that the hypothesis is accepted. Based on multiple linear regression analysis, it shows that all independent variables simultaneously have a significant effect on capital expenditure during the pandemic (Covid 19) in Sleman Regency, so the hypothesis is declared correct. Keywords: Regional Original Revenue (PAD), General Allocation Fund (DAU), Special Allocation Fund (DAK), Capital Expenditure.